PENGARUH SISTEM BIROKRASI TERHADAP PERILAKU PEGAWAI DALAM MENGIMPLEMENTASIKAN KEBIJAKAN SISTEM AKUNTABILITAS KINERJA INSTANSI PEMERINTAH : (Studi Pada BPS Di Wilayah Maluku Utara) - Fiqih Widiar Oktasari (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2023)
The Effect of the Bureaucratic System on Employee Behavior in Implementing Government Agencies Performance Accountability System Policies (Study at BPS in the North Maluku Region). SAKIP is a concept of a paradigm shift from Old Public Administration to New Public Management that. adapted by Indonesia from developed countries such as the United States, South Korea and New Zealand. The concept of this paradigm shift is a form of improving the quality of service to the public. However, accountability for performance in Indonesia is still weak in its implementation and there are still some of problems encountered in the implementation such as the bureaucratic system and the behavior of bureaucrats in implementing it. This study aims to determine whether the bureaucratic system influences the behavior of employees in implementing the SAKIP policy at BPS work units in the North Maluku region. This study uses a quantitative method with SEM-PLS analysis. The results of this study indicate that the bureaucratic system and employee behavior influence implementation. Then the employee behavior variable plays a role in mediating the influence of the bureaucratic system on the implementation of SAKIP in BPS work units in the North Maluku region